Cucker-Smale Flocking with Bounded Cohesive and Repulsive Forces. (30th September 2013) - Song, Qiang; Liu, Fang; Cao, Jinde; Qiu, Jianlong
Abstract : This paper proposes two Cucker-Smale-type flocking models by introducing both cohesive and repulsive forces to second-order multiagent systems. Under some mild conditions on the initial state of the flocking system, it is shown that the velocity consensus of the agents can be reached independent of the parameter which describes the decay of communication rates. In particular, the collision between any two agents can always be avoided by designing an appropriate bounded repulsive function based on the initial energy of the flock. Numerical examples are given to demonstrate the effectiveness of the theoretical analysis.